2010
DOI: 10.1016/j.jneb.2008.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Screen-related Sedentary Behaviors: Children's and Parents' Attitudes, Motivations, and Practices

Abstract: Objective-To investigate school-aged children's and parents' attitudes, social influences, and intentions toward excessive screen-related sedentary behaviour (S-RSB).Design-A cross-sectional study using a survey methodology.Setting-Elementary schools in London, Ontario, Canada.Participants-All grades five and six students, their parents and teachers in the participating schools were invited to voluntarily participate; 508 student-parent pairs completed the surveys. Main Outcome Measure-Children's screen-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
2
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 29 publications
(30 reference statements)
7
90
2
10
Order By: Relevance
“…These averages indicate a gender difference in screen time, similar to other studies. 24,30,31 Indeed, the girls averaged significantly (F = 32.351, df = , p < 0.0005) less screen time than the boys did. Of girls and boys, 61.8% and 70.0% exceeded the AAP's screen time recommendation, respectively.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…These averages indicate a gender difference in screen time, similar to other studies. 24,30,31 Indeed, the girls averaged significantly (F = 32.351, df = , p < 0.0005) less screen time than the boys did. Of girls and boys, 61.8% and 70.0% exceeded the AAP's screen time recommendation, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…In accordance with other research 17,24 that requested participation from parents regarding children's screen time, 2,759 questionnaires were filled out by mothers (87.6%). The vast majority of children had TVs, followed by computers, video game consoles, and cell phones in that order, as reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also felt that parents should serve as good role models for their children, a perception that is validated as parents and families play a key role in influencing most aspects of children's behavioural patterns 9 . In fact, our data indicated that sedentary activities primarily took place at home; children spent 3.4 hours per day engaged in S-RSB, and only 30 of these minutes occurred during school hours 10 .…”
Section: Discussionmentioning
confidence: 72%